Effect of processing routes on microstructure, electrical and dielectric behavior of Mg-doped CaCu3Ti4O12 electro-ceramic - Singh L.; Rai U.S.; Mandal K.D.; Rai A.K. (My University, 2025)
In the present communication, data on magnesium-doped calcium copper titanate CaCu2.90Mg0.10Ti4O12 (CCMTO) electro-ceramic, synthesized by the semi-wet route (SWR), ball-milled route (BMR) and solid-state route (SSR), is characterized by TG-DTA, XRD, SEM, EDX and TEM techniques. XRD confirmed the formation of single phase in CCMTO ceramic. The CuO phase present at grain boundaries in SWR ceramic was shown by the SEM micrograph, which was verified by EDX. The TEM image of SWR ceramic shows nanocrystalline particles in the range 80±20 nm. The value of the dielectric constant of SWR (ε r ∼20091) ceramic is higher than those of BMR and SSR (ε r ∼1247) ceramics at 1 kHz at 450 K. A dielectric relaxation has been observed in the frequency range 100 Hz-100 kHz. The high-temperature dielectric dispersion shows one large low-frequency response and two Debye-type relaxations. The impedance and modulus studies show the highest grain-boundary resistance for BMR ceramic. © 2012 Springer-Verlag Berlin Heidelberg.